Optimizing the soil physical environment toward greater crop yields - Hillel, Daniel (Academic Press, 1972)
This book presents papers that were given at a special invitational panel on the topic " Optimizing the soil physical environment toward greater crop yields", convened as part of the international symposium on soilwater physics and technology.